Sumaúma: estação de monitoramento de plantas domésticas utilizando android e esp32 - Bentes, Ariel Luane Pereira (Brasil, 2023)
Monitoring of houseplants through apps on Android devices has become a growing trend among gardening enthusiasts. These applications offer a practical and convenient solution to assist in plant care, combining a passion for nature with advances in mobile technology. This work presents the initial stage of development of a tool aimed at facilitating control, monitoring, and automation of plant cultivation in residences. In this context, a mobile application for Android was developed, which allows real-time data collection from sensors of an embedded device (Esp32) associated with a plant. These sensors monitor brightness, humidity, temperature, and soil moisture. The Android application displays the collected data in a simple and intuitive manner, enabling users to visualize and analyze them.